Space jam: Are niche parties strategic or looney?. (December 2015) - Tromborg, Mathias Wessel
Abstract: There is an emerging consensus that niche parties are fundamentally different from mainstream parties because niche parties do not moderate their policy positions strategically. However, there is theoretical reason to believe that niche parties have an electoral incentive to shift their policy positions in the same direction as parties that are proximate to them in their most salient policy space. This paper examines whether niche parties respond to such electoral incentives, using data on government coalitions from the Parliament and Government Composition Database, and party behavior from the Comparative Manifesto Project in 17 Western style democracies. The results suggest that niche parties tend to respond strategically to the perceived behavior of proximate parties, especially on their most salient policy dimension. Highlights: I challenge the emerging consensus that niche parties do not moderate their positions strategically on two counts. First, it has not been shown whether niche parties shift their policy positions in the same direction as proximate parties. Second, niche parties have been examined in the left-right ideological space where they may not compete. I find that niche parties respond to the behavior of proximate parties in their most salient policy space.